Effects of Video-Dubbing Creations (Using Peer Instruction Approaches) on Learning Achievement, Willingness to Communicate and Learning Anxiety - Ching Chang; Hui-Chin Yeh (The EUROCALL Review)
This study investigated willingness to communicate (WTC) and learning anxiety while immersing students in video dubbing (VDUB) activities using a peer instruction learning strategy. A total of 63 students participated in the study. The control group (CG) of 33 students used a teacher-led VDUB learning method, while the experimental group (EG) of 30 students adopted a peer instruction VDUB learning method. The study attempted to explore the differences between English learning achievement and WTC, as well as the perspectives of language learning anxiety. Results showed that the English learning achievement of the EG was superior to that of the CG in the final performance of VDUB creation, and in WTC (both between-group interaction and student-to-whole class interaction). The EG’s learning anxiety was lower than the CG’s. The implications of the research are discussed and suggestions for future research made.